Penyuluhan Gerakan Cinta Tubuh Melalui Pola Hidup Bersih dan Sehat Pada Siswa SDN Perwira IV Kota Bekasi - Syifah, Dinda Nuriyah; Mun Nia, Indah Anggun; Satifah, Dina; Yuliyanah, Yuliyanah; Putri, Fara Diba Catur; Maharbid, Dian Anggraeni (STIKES Yayasan RS.Dr.Soetomo, 2025)
This outreach activity is in collaboration with one of the elementary school education agencies, namely SDN Perwira IV, Bekasi City. The object of counseling in this research is all class V students. The method used is an outreach method about Clean and Healthy Lifestyles in which there are several activities ranging from presentation of material to practice carried out by students. Based on the results of the activities carried out, students are able to know how to wash their hands properly and correctly, get used to consuming healthy and nutritious food, and how to brush their teeth properly and correctly. In conclusion, students already know and are able to implement a Clean and Healthy Lifestyle (PHBS) in the school environment.